The Effect of Roasting and Baking Cowpeas on the Moisture Content, Physical Properties, and Organoleptic Properties of Nut Cakes: Pengaruh Sangrai dan Pemanggangan Kacang Tunggak terhadap Kadar Air, Sifat Fisik, dan Organoleptik Kue Kacang - nur, Chofifah; Hidayati, Laili; Kiranawati, Titi Mutiara; Saputri, Anggi Martiningtyas Januwati (Fakultas Industri Kreatif Universitas Surabaya, 2025)
Many local nuts are found in Indonesia. One type of nut that can be used as an innovation in making cookies is cowpea. This research aims to observe the differences in the process of making cowpea flour using roasting and oven methods in terms of moisture content, physical characteristics (color and texture), and organoleptic assessment. This experimental research used a 100% percentage and was repeated twice for making cowpea cookies. Data were analyzed using a t-test. The results showed that the roasting and oven methods in the process of grinding cowpea flour significantly affected the physical characteristics of color but did not affect moisture content and texture. In terms of organoleptic properties, including color, aroma, taste, and texture, panelists tended to prefer cookies made with roasted cowpea flour. Overall, cookies made with roasted cowpea flour were rated to have better organoleptic results compared to those made with oven-dried cowpea flour.